Climate change effects on dengue transmission in Malaysia: a review - Anua, Siti Marwanis; Hassan, Noor Artika; Mohd Fauzi, Ahmad Idlan; Kamaludin, Ahmad Muhaimin; Azmi, Asif Fikri; Mohd Yazid, Muhammad Luqman Haqim (Penerbit UTM Press, 2023)
Climate change remains a pressing global issue, with vast magnitude and detrimental effects on various aspects, including public health. Among the consequences of climate change, dengue fever is one of the vector-borne diseases projected to witness an increase in incidence due to alterations in transmission dynamics. This review aims to delve into the current understanding of how climate change impacts dengue transmission in Malaysia. The methodology involved the identification of relevant studies from three databases (PubMed, Scopus, and EBSCO) spanning the years 2013 to 2023, followed by a screening process based on predetermined inclusion and exclusion criteria. Ultimately, nine studies were included in the review, with temperature, precipitation, and humidity emerging as the three most extensively studied climatic variables, all of which demonstrated a significant correlation with dengue incidence. Given the evidence presented in numerous articles, it is imperative for policymakers to undertake essential policy revisions to confront this global challenge effectively and to demonstrate resolute and dedicated action in addressing this matter.